Airway anomalies in patients with craniosynostosis. (19th November 2018) - Mathews, Fasil; Shaffer, Amber D.; Georg, Matthew W.; Ford, Matthew D.; Goldstein, Jesse A.; Jabbour, Noel; Simons, Jeffrey P.
Abstract : Objectives: 1) Characterize the spectrum of airway anomalies in patients with craniosynostosis, and 2) identify clinical characteristics of these patients that may be associated with the development of airway anomalies. Methods: This study is a retrospective case series assessing the type and frequency of airway anomalies in all patients with craniosynostosis seen at a tertiary‐care children's hospital between 2000 and 2016. Cohort analyses were then performed to identify differences in airway anomalies dependent on syndromic associations, multisutural fusion, and location of suture fusion. Clinical characteristics examined included demographics and additional neurologic and craniofacial abnormalities. Results: Four hundred and ninety‐six patients with craniosynostosis (83.5% white, 64.5% male; 33.9% sagittal, 28.8% metopic, 11.5% coronal, 1.2% lambdoid, and 24.6% multisutural) were included. Notable airway anomalies included the following: 13.3% adenotonsillar hypertrophy, 8.9% laryngomalacia, 7.3% tracheomalacia, 7.1% subglottic stenosis, 4.0% bronchomalacia, 3.8% laryngeal cleft, and 1.2% vocal fold paresis. Multisutural craniosynostosis patients (n = 122) were more likely to have obstructive sleep apnea ( P = 0.005), adenotonsillar hypertrophy ( P = 0.014), tracheomalacia ( P = 0.011), subglottic stenosis ( P < 0.001), and epiglottic/base of tongue collapse ( P = 0.003) and require tracheostomy ( P = 0.001) and mechanical ventilation ( P = 0.017) compared with single suture craniosynostosis. Syndromic craniosynostosis patients (n = 33) were more likely to have obstructive sleep apnea ( P < 0.001), laryngomalacia ( P = 0.047), and subglottic stenosis ( P = 0.009) compared with nonsyndromic patients. Conclusion: Airway anomalies are prevalent in patients with craniosynostosis; patients with multisutural or syndromic types have an increased risk of developing certain abnormalities. There should be a lower threshold for referral for airway evaluation in these populations. Level of Evidence: 4. Laryngoscope, 129:2594–2602, 2019